Increasing Growth of Lettuce and Mizuna under Sole-Source LED Lighting Using Longer Photoperiods with the Same Daily Light Integral - Shane Palmer; Marc W. van Iersel (Agronomy, 2020)
Light recommendations for horticultural crops often focus on the optimal daily light integral (DLI) without regard to how that light is delivered throughout each day. Because photosynthesis is more efficient at lower photosynthetic photon flux density (PPFD), we hypothesized that longer photoperiods with lower PPFD results in faster growth than shorter photoperiods with higher PPFD and the same DLI. We quantified the effect of different photoperiods, all providing the same DLI, on photosynthesis and growth of two leafy greens. Mizuna (Brassica rapa var. japonica) and lettuce (Lactuca sativa) “Little Gem” were grown from seed in a controlled environment chamber (20 °C and 819 µmol·mol−1 CO2) under six photoperiods (10, 12, 14, 16, 18, and 20 h). LED fixtures provided white light and PPFD was adjusted so each treatment received a DLI of 16 mol·m−2·d−1. Mizuna and lettuce were harvested 30 and 41 days after planting, respectively. Longer photoperiods with lower PPFD increased light interception, chlorophyll content index, quantum yield of photosystem II, and aboveground biomass, but decreased instantaneous CO2 assimilation of lettuce and mizuna. Aboveground biomass increased 16.0% in lettuce and 18.7% in mizuna in response to increasing the photoperiod from 10 to 20 h. In summary, extending the photoperiod and lowering PPFD increases growth of lettuce and mizuna by increasing light interception and the quantum yield of photosystem II.